A produção do conhecimento sobre o PROEJA: análise de dissertações produzidas no estado do Paraná (2008-2013) - Caetano, Silvia Horwat de Morais (2014)
We conducted this study to analyze the dissertations in the Graduate Programs in Education of the State of Paraná discussing the National Integration Program of Professional Education in the Middle School Modality Youth and Adult Education - PROEJA , seeking to identify the ideas presented in around the theoretical assumptions , the evaluation of the implementation and evaluation of policy in order to ascertain to what extent consider the political, economic and social assumptions on which it is produced and implemented the program . Our research has addressed, in particular, the essays that comprise the Project Leads and Potentials of PROEJA in Paraná State. We analyzed nine dissertations in this project which brought together researchers from the Graduate Program in Technology - PPGTE / UTFPR - Federal Technological University of Paraná, the Graduate Program in Education - PPGE / UFPR - Federal University of Paraná and Program Postgraduate Education - PPGE / UNIOESTE - State University of West Paraná. Our work rated dissertations from four categories you deem relevant to understand the political, economic and social assumptions of PROEJA: work as an educational principle, integrated curriculum, policy implementation and evaluation, and avoidance. Given the objectives presented in the introduction, we present our research reporting how was the definition of our object of study, the organization of work, reflections on the state and social policies and the above categories in order to analyze the dissertations. In the second chapter, we tried to rescue the history of youth and adult education in Brazil as well as some notes on vocational education. Still, in this chapter, we make an explanation about PROEJA and some of the assumptions that guide their deployment and implementation. In the third chapter, we present, in fact, the nine essays that make up the Project Leads and Potentials of PROEJA in Paraná State, pointing your route and conclusions. In the fourth and final chapter, organized in a final consideration, we try to reconstruct the route of analysis developed and rescue the proposed questions and persecuted during the research seeking to clarify how the above categories help us to identify the theoretical assumptions, the evaluation of the implementation and evaluation of policy PROEJA.